Physical and Chemical Characteristics of Maleo Egg in Bogani Nani Wartabone Park - Saerang, JLP; Manalu, W; Soesanto, IRH; Mardiastuti, A (ANIMAL PRODUCTION, 2010)
The objective of this study was to examine the size (weight, length, and width) of Maleo egg in Bogani Nani Wartabone National Park.Physical characteristics that measure are : egg weight, egg shell, egg index , yolk, and albumen. Physical characteristics measured were: egg weight, egg shell thickness, egg index, yolk, and albumen. Two fresh eggs were weighed to the electric ohause balance with 400 g the scale 0.01. Two fresh egg were weighed with an electric balance. Length and width off egg were measured by used vernier caliper, egg shell thickness byÂ  tripod micrometer, yolk color by yolk color fan. Length and width of egg used were measured by Vernier caliper, and egg shell thickness by a tripod micrometer, yolk color by yolk color fan. Physical characteristic have been identified eggs weight, egg width, egg length, egg index, albumen width, albumen length, albumen index, yolk width, yolk length, yolk index, weight albumen, weight yolk, egg shell thickness, and shell weight increased by 223.70 g, 104.00 mm, 56.68 mm, 56.41, 113.8 mm, 86.72 mm, 6.07%,Â  85.30 mm, 69.90 mm, 31.54%, 47.51 g, 110.80 g, 0.02 inch, 19.55 g, respectively. The result of analysis indicated that maleo eggs have completed amino acids and fatty acids, that is essensial amino acids, non essensial amino acids, saturated fatty acids and unsaturated fatty acids. Physical characteristic egg that comprised of egg weight, egg width, egg length, egg index, albumen width, albumen length, albumen index, yolk width, yolk length, yolk index, albumen weight, yolk weight, egg shell thickness, and shell weight were 223.70 g, 104.00 mm, 56.68 mm, 56.41, 113.8 mm, 86.72 mm, 6,07%, 85.30 mm, 69.90 mm, 31.54%, 47.51 g, 110.80 g, 0:02-inch, 19:55 g, respectively. Maleo egg contained complete amino acids and fatty acids, including essential amino acids, non essential amino acids, saturated fatty acids and unsaturated fatty acids. (Animal Production 12(1): 34-38 (2010)Key Words: Maleo bird, maleo egg, physical characteristics, chemical characteristics